From Hyper to Aware: Strategi Promosi Kesehatan tentang Hipertiroidisme pada Remaja SMK - Muhammad Deri Ramadhan; Theophylia Melisa Manumara; Desti Alfiana; Bunga Riase Amalia; Davina Apandi Putri; Novy Alawiyah; Salwa Fadhila Oktaviani Solihin; Dhea Lestari; Nabila Zalfa; Nur Aeni Mukti; Tiara Andita Septiani; Farla Meitha Zahra; Albar Rizky Suwita (Jurnal Medika: Medika, 2026)
Hyperthyroidism is a condition characterized by excessive production of thyroid hormones, leading to increased metabolic activity and symptoms such as weight loss, palpitations, tremors, and emotional disturbances. This condition can affect various body systems and potentially cause serious complications if not properly managed. Knowledge among adolescents regarding hyperthyroidism and its risk factors remains low, making health education important to increase awareness and early prevention. The method used in this study was a literature-based approach by reviewing sources from online databases such as PubMed and Google Scholar to collect information related to the mechanisms, symptoms, and prevention of hyperthyroidism. The results indicate that proper health education can improve adolescents’ understanding of hyperthyroidism and encourage the adoption of healthy lifestyle behaviors. In conclusion, increasing access to health information and continuous education can enhance awareness among students, thereby supporting early detection and prevention of hyperthyroidism in the future.